Unsustainable trajectories of domestic information technology use in Australia: Exploring diversity and the life course. Issue 4 (16th July 2018) - Lane, Ruth; Follett, Kaye; Lindsay, Jo
Abstract : Current trajectories of the proliferation and use of information technology (IT) in households present an example of rapid socio‐technical change in an unsustainable direction. We document patterns in the proliferation, use and accumulation of IT in households in Australia, drawing on data from an online national survey ( N  = 1, 475) and qualitative interviews conducted during 2015 and 2016 ( N  = 36, with participants from three cities and one regional town). We identified cohorts of IT users who shared specific use practices and found that age, life course and income were important for defining and understanding these cohorts. IT practices change with life course transitions, such as children moving through the education system. Practices may be linked with changes in residence and income, and provide opportunities for interventions at such times when both technology and its use are changing anyway. The most concerning development was the use of multiple devices simultaneously, particularly when this included live streaming of high‐resolution video and audio. This practice is increasing in households with teenagers and young adults, and is likely, if unchecked, to become a significant driver of energy demand. We conclude by reflecting on the implications of our findings for (1) influencing current unsustainable trajectories of IT use into the future and (2) conceptualising the agency of householders in socio‐technical change involving fast‐changing technologies. There is an increasing research focus on the multiplicity of transition pathways, but a focus on the life course can, we argue, bring a new and important dimension to this understanding.